Effect of Red Bean Extract (Phaseolus vulgaris L. Sp) on Interleukin-1, Inhibin Β and PCNA Expression in Systemic Lupus Erythematosus Mice Model - Albert Novriadi; Muhammad Nooryanto; I Wayan Agung Indrawan; Puspita Handayani (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Systemic Lupus Erythematosus (SLE) is a complex autoimmune disease characterized by multiple organ involvement. Chronic inflammation due to oxidative stress and autoimmune causes damage to related organs, one of which is the ovary which leads to Premature Ovarian Failure (POF) . Red bean (Phaseolus vulgaris L. Sp.) is an anti-inflammatory and antioxidant agent. This study aims to examine the effect of red beans on IL-1, Inhibin B, and PCNA. Methods: This is a true experimental study with a post-test-only controlled group design in vivo. The sample in this study were female Balb/c mice treated with red bean extract (Phaseolus vulgaris L. sp.) at doses of 50 mg/KgBW (P1), 75 mg/KgBW (P2), and 100 mg/KgBW (P3). IL-1, Inhibin B, and PCNA levels in each group were statistically analyzed using the SPSS 16 for Windows software program. Results: Red bean extract (Phaseolus vulgaris L. Sp.) administration at various doses was statistically proven to significantly reduce IL-1 levels (p<0,05) and increase Inhibin levels in all groups (p<0,05). The highest average Inhibin B levels were found in the 100 mg/KgBW dose group (P3), significant increase in PCNA expression in all groups given various doses of red bean extract (p<0,05). Conclusion: Administration of red bean extract (Phaseoulus vulgaris L. Sp.) can reduce levels of Interleukin-1, increase levels of Inhibin B and PCNA expression in SLE mice.